2017
DOI: 10.1021/acsami.7b05842
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hybrid Collagen Aerogels Reinforced with Wheat Grass Bioactives as Instructive Scaffolds for Collagen Turnover and Angiogenesis for Wound Healing Applications

Abstract: The present study illustrates the progress of the wheat grass bioactive-reinforced collagen-based aerogel system as an instructive scaffold for collagen turnover and angiogenesis for wound healing applications. The reinforcement of wheat grass bioactives in collagen resulted in the design and development of aerogels with enhanced physicochemical and biomechanical properties due to the intermolecular interaction between the active growth factors of wheat grass and collagen fibril. Differential scanning calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…The pro-angiogenic properties and controlled anti-proteolytic activity of collagen-curcumin aerogels augmented their applications in biomedical field including restoration of damaged tissues. Govindarajan et al 45 reported the progress of the wheat grass bioactive compoundsreinforced collagen-based aerogel system as an instructive scaffold for collagen turnover and angiogenesis for wound healing applications. As shown in Figure 2, the study illustrated the therapeutic efficacy of bioactive compounds from wheat grass for wound healing.…”
Section: Aerogel-based Biomaterials For Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-angiogenic properties and controlled anti-proteolytic activity of collagen-curcumin aerogels augmented their applications in biomedical field including restoration of damaged tissues. Govindarajan et al 45 reported the progress of the wheat grass bioactive compoundsreinforced collagen-based aerogel system as an instructive scaffold for collagen turnover and angiogenesis for wound healing applications. As shown in Figure 2, the study illustrated the therapeutic efficacy of bioactive compounds from wheat grass for wound healing.…”
Section: Aerogel-based Biomaterials For Wound Healingmentioning
confidence: 99%
“…Wheat grass extract contains several bioactive constituents and has been reported to display potent antibacterial and antioxidant effects, which are beneficial for wound healing. 45,46 The bioactive compounds from wheat grass enhance the physicochemical and biomechanical properties of collagen aerogels with a 3D porous architecture similar to natural ECM. The sustained transportation of bioactive compounds across the aerogels to the cellular microenvironment displays antimicrobial and proangiogenic properties for enhanced wound healing.…”
Section: Aerogel-based Biomaterials For Wound Healingmentioning
confidence: 99%
“…Building on the knowledge developed collagen-fibrin composites [69] and goat tendon collagen aerogels [70], respectively.…”
Section: Synthesis Of Network Architectures To Achieve Dressing Multimentioning
confidence: 99%
“…Collagen-based composites displayed more than 40 wt.% mass loss following 24-hour incubation in enzymatic media, partially explained by the absence of any covalent crosslinks; yet, they induced accelerated healing of full thickness wounds in albino Wistar rats via suppression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthases (iNOS) and MMP-9 expressions [71]. On the other hand, triticum aestivum was shown to promote chemical crosslinking of collagen lysines [70], so that triticum aestivum-loaded collagen aerogels displayed proangiogenic effect resulting in complete wound closure in female wistar rats following 18 days post-wounding. Besides the biochemical modulation of the wound microenvironment, sponges of denatured collagen and hyaluronic acid were realised and loaded with epidermal growth factor (EGF), aiming to stimulate cell proliferation for the treatments of burns [72].…”
Section: Synthesis Of Network Architectures To Achieve Dressing Multimentioning
confidence: 99%
“…It has been obtained from different sources including rat tail, fish, bovine, ovine, or porcine (Ghodbane & Dunn, ; Pal et al, ). Additionally, it has been used with the intention to deliver certain drugs or biomolecules (Li et al, ; Wang, Thibaud, & Helary, ) that contribute to the healing process or limit and prevent microbial colonization of the wound using mainly antibiotics (Alvarez et al, ; Hall Barrientos et al, ) or natural products (Govindarajan et al, ; Kandhasamy et al, ). However, collagen scaffolds often present poor mechanical properties, high susceptibility to degradation and low capacity to incorporate hydrophobic drugs making necessary physical and chemical modifications to improve their properties (Perumal et al, ; Ward, Kelly, Wang, Zeugolis, & Pandit, ).…”
Section: Introductionmentioning
confidence: 99%